High‐Angular Resolution Electron Backscatter Diffraction as a New Tool for Mapping Lattice Distortion in Geological Minerals. Issue 7 (6th July 2019) - Wallis, D.; Hansen, L. N.; Britton, T. B.; Wilkinson, A. J.
Abstract: Analysis of distortions of the crystal lattice within individual mineral grains is central to the investigation of microscale processes that control and record tectonic events. These distortions are generally combinations of lattice rotations and elastic strains, but a lack of suitable observational techniques has prevented these components being mapped simultaneously and routinely in earth science laboratories. However, the technique of high‐angular resolution electron backscatter diffraction (HR‐EBSD) provides the opportunity to simultaneously map lattice rotation and elastic strain gradients with exceptional precision, on the order of 0.01° for rotations and 10 −4 in strain, using a scanning electron microscope. Importantly, these rotations and lattice strains relate to densities of geometrically necessary dislocations and residual stresses. Recent works have begun to apply and adapt HR‐EBSD to geological minerals, highlighting the potential of the technique to provide new insights into the microphysics of rock deformation. Therefore, the purpose of this review is to provide a summary of the technique, to identify caveats and targets for further development, and to suggest areas where it offers potential for major advances. In particular, HR‐EBSD is well suited to characterizing the roles of different dislocation types during crystal plastic deformation and to mapping heterogeneous internal stress fields associated with specific deformation mechanisms/microstructures or changes in temperature, confining pressure, or macroscopic deviatoric stress. These capabilities make HR‐EBSD a particularly powerful new technique for analyzing the microstructures of deformed geological materials. Key Points: HR‐EBSD uses cross correlation of diffraction patterns to map lattice distortion Rotations and strains can be used to calculate GND densities and residual stresses, respectively Recent developments in data analysis make HR‐EBSD suitable for a wide range of rocks